E-Service Quality and E-Wom Regarding Consumer Behavior Based on Maqashid Asy-Shariah - Hayati, Mardhiyah; Ali, Juhary; Heri, Mad; Utami, Pertiwi (Journal of Digital Marketing and Halal Industry, 2023)
The E-commerce usage service quality index is the lowest among other parameters. The purpose of the study investigates the effect of e-Service Quality and e-WOM on consumer behavior using the maqasid ash-shariah approach. This research uses quantitative methods with an associative statistical approach. The results showed that e-service quality and e-WOM have a positive influence on consumer behavior. This means that when the e-service quality and Electronic Word of Mouth variables increase, so does the consumer behavior variable to make purchases in e-commerce transactions. The novelty of this research is the development of marketing management theory from the perspective of Islamic Economics in the digital era. Theoretical implications show that choosing the right e-service quality and e-WOM results in a positive response to the service quality of e-commerce users. From the perspective of Islamic Economics, the values of maqashid asy-syari'ah can influence the goal of achieving human welfare. So that all needs for goods/services have a benefit for human needs, be it dharuriyah, hajiyah and taxiniyah. The results of this research can be used as input for the Government to improve Electronic System Operator (PSE) services. So that later e-commerce can provide even better services.